2021
DOI: 10.3390/ijerph18157800
|View full text |Cite
|
Sign up to set email alerts
|

The WOMEN-UP Solution, a Patient-Centered Innovative e-Health Tool for Pelvic Floor Muscle Training: Qualitative and Usability Study during Early-Stage Development

Abstract: e-Health may enhance self-management of pelvic floor muscle training (PFMT) to treat stress urinary incontinence (SUI). It is crucial to involve patients in planning, developing and monitoring the optimal e-Health solution. This research aims to describe patient-centered innovation in an early developmental stage of the WOMEN-UP solution. We conducted a qualitative study through a self-developed questionnaire in 22 women with SUI, to define system requirements from a patient’s perspective. The first prototype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…video visits, phone calls, applications/internetbased treatments) have been largely effective in urology. [5][6][7] From the patient perspective, Locke et al conducted a survey of patients who received telemedicine consults in urology, and found that almost half had no preference for in-office versus telephone visits. 8 Other studies have found that some patients preferred telemedicine, owing to spending less time waiting to see practitioners, travelling to appointments, and eliminating the need to find transportation to attend appointments.…”
Section: ) What Are the Benefits And Limitations Of Virtual Platforms...mentioning
confidence: 99%
See 1 more Smart Citation
“…video visits, phone calls, applications/internetbased treatments) have been largely effective in urology. [5][6][7] From the patient perspective, Locke et al conducted a survey of patients who received telemedicine consults in urology, and found that almost half had no preference for in-office versus telephone visits. 8 Other studies have found that some patients preferred telemedicine, owing to spending less time waiting to see practitioners, travelling to appointments, and eliminating the need to find transportation to attend appointments.…”
Section: ) What Are the Benefits And Limitations Of Virtual Platforms...mentioning
confidence: 99%
“…22 One emerging area of virtual care is the use of app-based treatments for patient guidance and self-management. [5][6][7] For certain patients, these can be used effectively for management, such as in the case of stress urinary incontinence. 5-7…”
Section: © 202canadian Urological Associationmentioning
confidence: 99%
“…Just over 40% (12/28, 43%) of these were solely mobile apps, 4% (1/28) trialed a smartphone-based messaging system, 11% (3/28) were internet-based programs, and 7% (2/28) were dedicated to videoconferencing. A total of 32% (9/28) of the technologies involved the use of a portable vaginal biofeedback or accelerometer-based device [36][37][38]43,44,48,49,53,54,62,67,71,76] that provided real-time feedback transmitted via Bluetooth to a mobile app or, in one instance, to a computer application [43]. In addition to the vaginal device, electromyographic data were integrated from surface electrodes attached to the abdominal muscles [37,38] or PFMs [36].…”
Section: Types Of Dts (Consensus On Exercise Reporting Template For P...mentioning
confidence: 99%
“…A total of 21% (6/28) of the DTs incorporated gamification [36][37][38]48,57,67], which, with 1 exception [57], was used in conjunction with biofeedback. Descriptions of gamification included "serious games" [37,38], games or activities (eg, weight lifting room and flying arena) [67], and gaming and virtual reality mediated by a comic character [11,57] or a cyclist [36] with built-in scoring systems.…”
Section: Social Media and Gamificationmentioning
confidence: 99%
See 1 more Smart Citation